Size and distributional pattern of pension-related tax expenditures in European countries - Salvador Barrios; Flavia Coda Moscarola; Francesco Figari; Luca Gandullia (European Commission, Joint Research Centre (JRC), 2018)
Policy discussions on pension systems generally focus on their sustainability and design, including retirement age, income reference and contributory period while relative little attention is devoted to the tax treatment of pension contributions and pension benefits. However, tax expenditures - defined as deviations from an agreed benchmark tax system - are widely used in the EU Member States and little is known on their redistributive or fiscal impact. This paper quantifies the fiscal and distributional impact of tax expenditures related to public and private contributory pension schemes, affecting both contributions and pension benefits, in 28 European countries using EUROMOD, the EU-wide microsimulation model. We find that pension-related tax expenditures can have a sizeable revenue impact and strong effects on inequality and poverty. Moreover tax expenditures tend to be progressive at two levels. First, among elderly, favoring lower income pensioners, mainly through a favorable treatment of pension incomes. Second, among working-age individuals, through partial or no deduction of pension contributions, draining resources from those at the top of the income distribution.
Keywords: 330; EUROMOD; pensions; tax expenditures; inequality; taxation; fairness; life cycle